PEMANFAATAN KEGIATAN MENULIS JURNAL SEBAGAI BAHAN PENILAIAN AUTENTIK DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS XII TAHUN PELAJARAN 2017-2018 - Mike Mike (Eksponen, 2020)
Based on observations and experiences in class, it was found that writing is often a matter of less interest and there is less good response from students. Writing skills in the classroom are generally taught only when learning to write, writing skills should be integrated in learning or inserted in every learning in class. Problems that also arise related to learning writing skills in schools are the way to assess and target curriculum achievement which is only measured based on the results of written tests. Because of this, it is necessary to apply an authentic writing skills assessment model that is in accordance with various techniques and procedures. The subjects in this research were the process of teaching and learning activities between students and teachers / researchers of Class XII MIPA 1 of SMAN 3 Kotabumi, North Lampung Regency in the Academic Year of 2017 - 2018, amounting to 34 students. After conducting research and analyzing research data, the researchers concluded that the use of journal writing skills as an authentic assessment material in Indonesian Language Subjects Class XII MIPA 1 SMA Negeri 3 Kotabumi can improve student learning outcomes. This is evidenced by the increase in the percentage of Minimum Completeness Criteria that have been determined from the first cycle to the second cycle of 23.69%.